Γεωπονικό Πανεπιστήμιο Αθηνών (Γ.Π.Α) (Agricultural University of Athens (official channel), 2017)
: Παρακαλώ, ευχαριστώ! That's not my fate, that's not your land Rising up that case can be destroyed Can be exhausting, but a smile comes when they grow old Restless thoughts and options you're so proud of when you know Or if you don't they disappear and they feel wrong And they feel wrong, and they feel wrong Right, you look up right again You broke your right to be the same like them I want them real, I want them to live their life in peace Lost, you seem to hesitate My thoughts are black, your ones are reprimand I want you cool, I want you live Your life in colors Carve your name on fences, walls or seats The road you walk has just a street But there are a lot of hidden roads Rising up that case can be destroyed Can be exhausting, but a smile comes when they grow old Restless thoughts and options you're so proud of when you know Or if you don't they disappear and they feel wrong Right, you look up right again You broke your right to be the same like them I want them real, I want them to live their life in peace Lost, you seem to hesitate My thoughts are black, your ones are reprimand I want you cool, I want you live Your life in colors I want them real, I want them to live Your life in colors